MULTI-RESPONSE OPTIMIZATION OF TRANSESTERIFICATION PARAMETERS OF COTTON SEED OIL USING GREY RELATIONAL ANALYSIS IN TAGUCHI METHOD FOR QUENCHING APPLICATION - Dodo, R. M.; Ause, T.; Dauda, E. T.; Shehu, U.; Hayatudeen, I. A. (FUDMA JOURNAL OF SCIENCES, 2020)
The present investigation involves Taguchi Grey relational analysis-based optimization of transesterification process parameters such as methanol to oil molar ration, catalyst loading and temperature and their effect on both per cent fatty acid methyl ester (FAME) yield and heat transfer coefficient (HTC) of transesterified cotton seed oil (TC). A Taguchi L9 orthogonal array was designed and nine experimental runs were conducted based on the designed experiments. The FAME (ester) yield and HTC were recorded for each experiment. Based on the average responses computed from Taguchi grey relational analysis, methanol to oil molar ration of 9:1 (32.6 wt% of methanol), catalyst loading of 0.5 wt% and temperature of 60 oC were identified to be the optimal parameters. Confirmation test conducted using the optimal parameters setting demonstrated an improvement of 0.3% in grey relational grade. Methyl ester group was detected in TC on 1438.8 cm-1 by FTIR spectra. Cooling curve analysis of the TC from the confirmation experiment indicated outstanding quenching performance compared to raw cotton seed oil (FC) and SAE40.